Risk Stewardship of Sindhung Warih Value in Sustainable Village Own Enterprise - Amerieska, Siti; Anik Kusnawati; Andi Kusuma; Riezky Amalia (Asian Journal of Management, Entrepreneurship and Social Science, 2025)
The purpose of this study is to explore risk management practices at Village Own Enterprise (VOE) . The qualitative research method in this research uses an explanatory case study approach . The analytical tool used is Stewardship Theory and PP No. 11 of 2021 concerning VOE and Enterprise Risk Management (ERM) to map the risks that occur in VOE The results of this study there are four types of risk namely; the first is strategic risk with indicators of governance, planning risk, market risk. The second is operational risk which consists of human resource risk, how monitoring and controlling are carried out. The three financial risks, in this case accounting and reporting, are processes that cannot be separated from fraud risk. The four sustainability risks are important by instilling risk awareness and supporting the mission of socio-cultural and environmental preservation in village communities. The research contribution provides guidance on what risks are faced by VOE as well as providing solutions on how VOE can survive and even their sustainability can be beneficial for the welfare of the community. There are 6 (six) VOE Sustainability values, consist of (1) Governance & Leadership Commitment, (2) Economic & Empowering Local Assets, (3) Stewardship cultural sindhung warih & Human Empowering, (4) Innovative, Network & Mutual Collaboration; (5) Environmin & Ecosystem Digitalize; (6) Risk Awareness & Compliance.